Glutamate levels in the ventromedial prefrontal cortex and resting‐state functional connectivity within reward circuits in alcohol‐dependent patients. (3rd March 2023) - Hu, Yiting; Dong, Fang; Xue, Ting; Zhou, Mi; Huang, Ruoyan; Sui, Feng; Guo, Qiang; Hou, Wenbao; Cai, Wenlong; Yuan, Kai; Wang, Hongde; Yu, Dahua
Abstract: Great progress has been made in understanding the neural mechanisms associated with alcohol‐dependent (AD) patients. However, the interactions within the reward circuits of the patients need further exploration. Glutamatergic projections from the prefrontal cortex to some brain regions are present in the reward circuit. However, little is known about the potential implications of glutamate levels in the prefrontal cortex on abnormal interactions within reward circuits in AD patients. To determine the potential roles of reward circuits in drinking, we investigated differences in resting‐state functional connectivity (RSFC) and multivariate Granger causality analysis between 20 AD patients and 20 healthy controls (HC). The neuroimaging findings were then correlated with clinical variables (alcohol use disorder identification test). The ventromedial prefrontal cortex (VmPFC) is believed to play a critical role in addiction disorders, and glutamatergic projections from the prefrontal cortex to several regions of the brain are present in reward circuits. Proton magnetic resonance spectroscopy was also performed to assess the difference in glutamate levels in VmPFC between AD patients and HC. The results showed that the strength of functional connectivity in the reward circuit was generally attenuated in AD patients, and the reciprocal enhancement of activity between the right insula, left thalamus and VmPFC was found to be significantly greater in AD patients. It is worth noting that although glutamate levels in the VmPFC did not show significant differences between the two groups, the level of glutamate in the VmPFC was significantly correlated with RSFC. We hope that the current findings will help us to develop new intervention models based on the important role of the VmPFC in AD. Abstract : This study found altered functional connectivity and GCA within reward circuits in alcohol‐dependent patients. Furthermore, glutamate levels in the ventromedial prefrontal cortex were significantly correlated with left thalamus connectivity among the participants. We hope that the current findings will help us to develop new intervention models based on the important role of the ventromedial prefrontal cortex in alcohol‐dependent patients